Morphological, genetic and pigment diversity of Nerium indicum Mill in Iran - Mohammadi, F.; Sharifi-Sirchi, G.; Samsampour, D. (Cellular and Molecular Biology, 2017)
The Nerium indicum Mill organs and parts of the 40 genotypes were sampled from 5 habitats of southand south east of Iran. In total, 15 morphological and pigmentvariables were measured. Analysis of variance was carried out based on completely randomized design and revealed significance differencesat p â‰¤ 0.05, 0.01 and 0.001 for the most variablesindicating a large-scale diversity among the genotypes. Cluster analysis divided the genotypes into 3 main groups. The first and second principal components had 34.73% and 18.67% of the variance, respectively. The main factors had 76.79% accumulated eigenvalue. Random amplified polymorphic DNA (RAPD) markers used to assess the population structure and genetic variation. In total, 361 polymorphic band amplified from effective 14 chosen RAPD markers. Analysis of molecular variance (AMOVA) showed 67% and 33% within and between populations genetic variation respectively. Cluster analysis by using UPGMA method divided genotypes into 6 main groups. A high cophenetic correlation coefficient (r = 0.90) was obtained. The first and second principle coordinates had 29.31% and 25.78% of the variance, respectively.